Analysis of Determinants of Virtual Currency and Portfolio Investment In Asean Countries - Indah Sari (Penerbit Jurnal Indonesia, 2025)
This study aims to analyze the influence of Customer Trust on This study aims to analyze the determinants of virtual currency and portfolio investment in ASEAN countries. The data used in this study is time series data in monthly form, from June 2020 to December 2021, while cross-sectional data is from four ASEAN countries (Indonesia, Malaysia, Singapore, and Thailand). The data analysis model uses panel regression. The results show that gold prices, interest rates, and exchange rates have a significant effect on virtual currency in ASEAN countries, while stock prices do not have a significant effect on virtual currency in ASEAN countries. Furthermore, interest rates, exchange rates, and virtual currency have a significant effect on portfolio investment in ASEAN countries, while inflation has no significant effect on portfolio investment in ASEAN countries.